Self-efficacy and sustainable rural tourism development: local communities’ perspectives from Kuching, Sarawak - Fong, S.-F.; Lo, May-Chiun; Peter, Songan; Nair, V. (Routledge, 2017)
The future of the tourism industry is dependent on local communities’ ability to develop and sustain tourism developments, especially in sensitive rural areas. But there is limited research on this topic to guide tourism authorities and governments. In particular, few studies have studied sustainable rural tourism development from the perspective of the local communities. Therefore, this study examines local communities’ views on their capability to achieve sustainable rural tourism development in selected rural areas in Kuching, Sarawak. Questionnaires were distributed to the local communities residing at three rural tourism destinations in Kuching, Sarawak. Interestingly, the results indicated that local communities’ self-efficacy has a positive relationship with social, cultural, economic, and environmental sustainability. Hence, this study offers theoretical and practical contributions to sustainable rural tourism development literature and the tourism industry.